2015
DOI: 10.5665/sleep.4422
|View full text |Cite
|
Sign up to set email alerts
|

SMART DOCS: A New Patient-Centered Outcomes and Coordinated-Care Management Approach for the Future Practice of Sleep Medicine

Abstract: http://www.clinicaltrials.gov, NCT02037438.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The “sustainable methods, algorithms, and research tools for delivering optimal care study” (SMART DOCS) is a PCORI-sponsored randomized, two-arm, single center, long-term comparative effectiveness study designed to compare a patient-centered and coordinated-care management approach with a conventional care approach in patients with sleep disorder complaints [113]. Features of the patient-centered approach include standardized intake (the Alliance sleep questionnaire which integrates other existing scales and questionnaires), use of novel technology, co-management with primary care, integration of multidisciplinary sleep team members for education and support, and enhanced patient–provider data and information sharing through a dedicated, easy-to-understand web-portal.…”
Section: Applying a Patient-centered Care Approach In Osa (See Table 1)mentioning
confidence: 99%
“…The “sustainable methods, algorithms, and research tools for delivering optimal care study” (SMART DOCS) is a PCORI-sponsored randomized, two-arm, single center, long-term comparative effectiveness study designed to compare a patient-centered and coordinated-care management approach with a conventional care approach in patients with sleep disorder complaints [113]. Features of the patient-centered approach include standardized intake (the Alliance sleep questionnaire which integrates other existing scales and questionnaires), use of novel technology, co-management with primary care, integration of multidisciplinary sleep team members for education and support, and enhanced patient–provider data and information sharing through a dedicated, easy-to-understand web-portal.…”
Section: Applying a Patient-centered Care Approach In Osa (See Table 1)mentioning
confidence: 99%
“…The rapid development of mobile health applications, secure messaging, and telemedicine platforms along with patient-centered and patient-navigator strategies are attractive and efficient options for delivering behavioral, educational, and supportive interventions to improve PAP adherence. [118][119][120] Home-Based versus Laboratory-Based Testing In two large randomized controlled trials, home-based diagnostic testing and PAP titration were comparable to laboratorybased diagnosis and manual PAP titrations in the management of OSA [121][122][123] and may be cost effective alternatives to full night polysomnography. 124 However, real-world Markov modelling suggest that laboratory polysomnography may be more cost-effective.…”
Section: Health Disparities In Osamentioning
confidence: 99%
“…It was observed that physical activity and exercise were related to higher quality sleep and less sleep disorders in healthy adults. Poor sleep quality and abnormal sleep durations (over or under 7-8 hours a day) were identified as being associated with morbidity and mortality (8). It was seen that exercising for more than one hour a day is associated with a longer duration of sleep and that low-intensity exercises had a positive influence on sleep (8).…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality and abnormal sleep durations (over or under 7-8 hours a day) were identified as being associated with morbidity and mortality (8). It was seen that exercising for more than one hour a day is associated with a longer duration of sleep and that low-intensity exercises had a positive influence on sleep (8). The sleep disorders in the older adults are related to an inactive lifestyle.…”
Section: Introductionmentioning
confidence: 99%